Some Linguistic Considerations on a New Celtiberian Bronze - Blanca María Prósper (Вопросы ономастики)
This work tackles a preliminary linguistic analysis of a new Celtiberian bronze in the Latin alphabet, probably dating back to the mid 1st c. BC. As usual with objects that remain in private hands and cannot be directly studied by professionals, doubts on its authenticity will predictably hover over any attempt to interpret it. However, many traits of the text merit comment. The onomastic and appellative material of the new bronze will prove instrumental in confirming the existence of a western Celtiberian dialect, spoken by the Arevaci, characterised by: a) early loss of final dental sounds; the only case of final - s, attes, goes back to a heteromorphemic sequence -t-s and must consequently be ascribed to the phoneme /sː/ (which had a tense articulation, probably a geminate in intervocalic position), reflected by -s in Early Celtiberian; b) monophthongisation of all instances of an inherited diphthong /ei̯/, shared by the rest of Celtic Hispania (<ei> reflects the emergence of secondary diphthongs: the forms diainim, aneittiq show the effects of the sound change -χt- > -i̯t- well known from Brittonic and Romance); c) final nasals haphazardly show up as -m, -n or are even omitted, which is suggestive of their weakness. By contrast, the tendency of the cluster -ti̯- to assibilation is not detectable. The study will also confirm that forms, including a number of proper names, hitherto poorly or not attested in Hispano-Celtic are, in fact, to be traced back to Proto-Celtic. It goes without saying, this bronze has not been cleaned and the readings may change over time, pending a thorough revision of better photographs or direct handling of the object.